2021
DOI: 10.1136/bmjopen-2021-049716
|View full text |Cite
|
Sign up to set email alerts
|

Science, healthcare system, and government effectiveness perception and COVID-19 vaccination acceptance and hesitancy in a global sample: an analytical cross-sectional analysis

Abstract: BackgroundDeterminants of COVID-19 vaccine acceptance are complex; how perceptions of the effectiveness of science, healthcare and government impact personal COVID-19 vaccine acceptance is unclear, despite all three domains providing critical roles in development, funding and provision, and distribution of COVID-19 vaccine.ObjectiveTo estimate impact of perception of science, healthcare systems, and government along with sociodemographic, psychosocial, and cultural characteristics on vaccine acceptance.DesignW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 38 publications
2
6
0
1
Order By: Relevance
“…This is contrary to the work of McSpadden ( 2022 ) and Al‐Hanawi et al ( 2021 ), who identified older people has concerns about the side effects and the effectiveness of the COVID‐19 vaccines. However, our results are similar to that of the international study conducted by Dye et al ( 2021 ), which identified individuals' attitude towards science, was a strong predictor of vaccine acceptance, than psychosocial or COVID‐19‐related variables, such as risk, due to age or co‐morbidities. In our study science was also identified as being more important than government effectiveness, as participants questioned the government's decisions on the rollout of the vaccine, but not the science supporting the vaccine.…”
Section: Discussionsupporting
confidence: 91%
“…This is contrary to the work of McSpadden ( 2022 ) and Al‐Hanawi et al ( 2021 ), who identified older people has concerns about the side effects and the effectiveness of the COVID‐19 vaccines. However, our results are similar to that of the international study conducted by Dye et al ( 2021 ), which identified individuals' attitude towards science, was a strong predictor of vaccine acceptance, than psychosocial or COVID‐19‐related variables, such as risk, due to age or co‐morbidities. In our study science was also identified as being more important than government effectiveness, as participants questioned the government's decisions on the rollout of the vaccine, but not the science supporting the vaccine.…”
Section: Discussionsupporting
confidence: 91%
“…According to our findings, adopting large-scale health efforts, such as mass vaccinations, requires government effectiveness and fiscal decentralization. Vaccine-related challenges are usually cited as reasons for government effectiveness in funding and distribution [44]. The government purchases, delivers, implements, and promotes immunization in most countries where COVID-19 vaccination is offered as a public service.…”
Section: Discussionmentioning
confidence: 99%
“…Effective governments may respond to the COVID-19 pandemic with integrated preparation, such as expanded testing and hospital facilities, monitoring, and distributing personal protective equipment and vaccines [43]. Dye et al [44] revealed that enhancing government effectiveness is essential, as vaccination coverage is only statistically significant in nations with solid government effectiveness. Governments with greater effectiveness may be able to target high-risk individuals and provide immunizations to maximize community health [45].…”
Section: Public Attitudes and Politicsmentioning
confidence: 99%
“…Communities with more significant pandemic-related risks are typically marginalized, and the lack of equitable access to information about COVID-19 is another layer exacerbating preexisting sociostructural determinants of health [ 10 ]. Misinformation, created by the politicization of COVID-19 and related public health measures, has magnified the pandemic’s challenges, including access to health care, vaccination and testing efforts, as well as personal protective equipment [ 11 ]. Of note, disparities are perpetuated by factors beyond the individual choices or preferences of community members.…”
Section: Introductionmentioning
confidence: 99%